Baking performance, rheology and physico-chemical properties of banana muffins substituted with crosslinked-tapioca starch - Julian, Mark Louie Callos
ABSTRACT This study was undertaken to determine the baking performance of crosslinked-tapioca starch substituted at 25% for all-purpose flour in a standard banana muffin formulation. The control muffin was made from all-purpose flour, leavening, iodized salt, margarine, buttermilk, sugar and banana. Likewise, rheological and physico-chemical analyses were conducted to assess possible changes in the batter and baked sample characteristics brought about by the incorporation of modified starch in the product. Volume measurements of the baked muffins suggested that the product substituted with 25% modified tapioca starch had a higher volume and was more peaked than the control as evidenced by both symmetry indices ad sensory evaluation. However, the muffin diluted with modified tapioca starch had a higher baking loss and was less dense in return. The density of the muffin, in agreement with specific volume determination, was lower than the control indicating a light grain with a greater acceptability of acceptance. The viscosity readings of the batter, taken in absolute centipoise, as well as the firmness of the baked product decreased upon the incorporation of modified starch in the standard muffin formulation. Substituted muffins resulted to products with higher moisture percentages and consequently, high Aw readings. Except for percent moisture and Aw, all other physico-chemical parameters (pH, % soluble solids and specific gravity) did not exhibit any significant difference between the two samples.